A nomogram model for predicting distant metastasis of newly diagnosed colorectal cancer based on clinical features - He, Jiang-Hua; Cao, Cong; Ding, Yang; Yi, Yun; Lv, Yu-Qing; Wang, Chun; Chang, Ying (Frontiers in Oncology, 2023)
Objective: Colorectal cancer is one of the most common primary malignancies and the third most common cause of cancer death in both men and women in the United States. Among people diagnosed with initial colorectal cancer, 22% had metastatic colorectal cancer, while the 5-year survival rate was less than 20%. The purpose of this study is to develop a nomogram for predicting distant metastasis in newly diagnosed colorectal cancer patients and to identify high-risk groups. Methods: We retrospectively reviewed the data of patients who were diagnosed as Colorectal cancer in Zhong nan Hospital of Wuhan University and People's Hospital of Gansu Province between January 2016 and December 2021. Risk predictors for distant metastasis from colorectal patients were determined by the univariate and multivariate logistic regression analysis. Nomograms were developed to predict the probabilities of distant metastatic sites of Colorectal cancer patients and evaluated by calibration curves, receiver operating characteristic curve, and decision curve analysis (DCA). Results: A total of 327 cases were included in this study, 224 colorectal cancer patients from Zhong nan Hospital of Wuhan University were incorporated into the training set, and 103 colorectal cancer patients from Gansu Provincial People's Hospital were incorporated into the testing set. By univariate logistic regression analysis, platelet level (PLT) (P=0.009), CEA level (P=0.032), histological grade (P<0.001), colorectal cancer tumor markers (P<0.001) and N stage (P<0.001), tumor site (P=0.005) were associated with distant metastasis in colorectal cancer patients. Multivariate logistic regression analysis showed that N stage (P<0.001), histological grade (P=0.026), and colorectal cancer markers (P<0.001) were independent predictors of distant metastasis in patients initially diagnosed with colorectal cancer. The above six risk factors were used to predict distant metastasis of newly diagnosed colorectal cancer. The C-indexes for the prediction of the nomogram were 0.902(95% confidence interval (CI), 0.857-0.948). Conclusion: The nomogram showed excellent accuracy in predicting distant metastatic sites and clinical utility may facilitate clinical decision-making. Keywords: Colorectal cancer; Distant metastasis; Prognosis; Nomogram; Platelet count